RESTORATIVE JUSTICE IN JUVENILE JUSTICE TO FORMULATE INTEGRATED CHILD CRIMINAL COURT - Hafrida, Hafrida (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
The purpose of this article is to formulate the concept of restorative justice which balanced to protect between child offenders and the victims through the diversion (Victim-offender oriented). This goal will be realized through normative research (legal research) based on Restorative Justice concept.Â In Law Number 11 of 2012 concerning the Child Criminal Justice System the process (SPPA Law), its prioritizes the Diversion Process (Settlement outside the court) carried out through a Restorative Justice approach. Article 5 paragraph (2) of the SPPA Law states Restorative Justice is the settlement of criminal cases by involving perpetrators, victims, families of perpetrators /victims, and other related parties to jointly to find a fair solution by emphasizing recovery and not based on revenge. Empirical conditions show that balanced legal protection between criminal offenders and victims has not implemented. Evaluation of Law Number 11 of 2012 is needed to formulating the Integrated Child Criminal Court.